Gereja dalam Realitas Sosial Indonesia Masa Kini - Ezra Tari; Jeni Isak Lele (JURNAL TERUNA BHAKTI, 2020)
This study aims to discover the function of the church in present-day reality. The church is confronted with self-actualization in today's complex context. The writer wants to show off the principle of the church which is constantly being renewed. The church as an organism is willing and able to transform social conditions. The method used in this research is qualitative research with a literature review approach. The approach emphasizes the research for theoretical studies and values that develop based on scientific studies. The writer concluded that the church must be involved in nation-building; renewal in all aspects of human life; the church contributes to upholding the law, human rights, and the role of women; the church becomes a place to uphold honesty, justice, and truth. Abstrak Kajian tulisan ini bertujuan menemukan fungsi gereja dalam realitas masa kini. Gereja diperhadapkan kepada reaktualisasi diri dalam konteks masa kini yang kompleks. Penulis hendak menyuarakan lagi prinsip gereja yakni terus-menerus diperbaharui. Gereja sebagai organisme mau dan mampu mentransformasi kondisi sosial. Cara yang digunakan dalam penelitian adalah prinsip kualitatif dengan pendekatan telaah literatur. Pendekatan menekankan penelusuran kajian teoritis dan nilai yang berkembang berdasarkan kajian ilmiah. Penulis memberi kesimpulan bahwa, gereja harus terlibat dalam pembangunan bangsa; pembaruan dalam seluruh aspek kehidupan manusia; gereja turut andil dalam menegakkan hukum, Hak Asasi Manusia, dan peran perempuan; gereja menjadi wadah menjunjung tinggi kejujuran, keadilan, dan kebenaran.